Il «duca Borso»: tra le pagine del satirico una scuola di formazione a Modena per giovani illustratori - Maria Letizia Paiato (Annali Online dell'Università di Ferrara. Sezione Lettere)
The article reconstructs the years of training of some artistic figures related to the city of Modena, who distinguished themselves in the illustration environment, in local satire and humor magazines published during the first decades of the twentieth century. In effect, in this period Modena was the most prolific city of the region in this specific field. Particular attention is given to the production of Umberto Tirelli, illustrator and founder of the well-known satirical magazine «il duca Borso». Casimiro Jodi, often concealed under the pseudonym of “Chiodi”, completed his apprenticeship there and became director in 1908. Towards the end of 1912 and throughout 1913 the very young Augusto Zoboli and Mario Vellani Marchi made their debut. The main attention of the essay is on Vellani Marchi, establishing, after extensive stylistic comparisons, his collaboration with the magazine, where he used to sign with the appellation of “Marius”.